A multicentre, randomized, double‐blind, parallel, active‐ and placebo‐controlled Phase 3 clinical study of the glucokinase activator PB‐201 in treatment‐naive patients with type 2 diabetes mellitus: A study protocol. Issue 3 (21st November 2022) - Du, Ying; Gao, Leili; Xiao, Xinhua; Hou, Xin; Ji, Linong
Abstract: Aim: To report the rationale for using PB‐201, a partial glucokinase activator (GKA), for a Phase 3 study (NCT05102149) assessing its efficacy and safety in a Chinese population and to describe the design of this GKA Phase 3 trial, the first to involve both an active control and a placebo control arm. Materials and methods: This is an ongoing, multicentre, randomized, double‐blind, three‐arm placebo and active control study to be carried out among 672 Chinese treatment‐naive participants with type 2 diabetes mellitus (T2DM) to assess the efficacy and safety of PB‐201 for approximately 60 weeks, including a screening period and a safety follow‐up period. Results: The primary objective of this study was to monitor change in glycated haemoglobin levels with PB‐201 in treatment‐naive T2DM participants from baseline to 24 weeks in comparison with vildagliptin and placebo. The key secondary objective was to assess the efficacy and safety of PB‐201 following treatment for a time period of 52 weeks. Conclusion: This pivotal study will offer critical information regarding the efficacy and safety of PB‐201 in Chinese treatment‐naive T2DM participants that would help to establish robust evidence for the benefit‐risk evaluation of this drug.